Do HIV positive people combining ARVs with immune boosters, traditional herbal medicines or vitamins experience viral resistance and treatment failure than those taking ARVs only? - Shweni, Nomakula Noluthando (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.